Prognostic value of the site, depth, and infection/ischemia classification system in diabetic foot ulcers: a retrospective cohort study - Chun-Hua Zhang; Chun-Yan Jiao; Li Li; Chen-Hui Sui; Ting Ji; Fan Wang; Jin-Jun Wang; Xiao-Na Liu (Scientific Reports)
Abstract Diabetic foot ulcers (DFUs) represent a significant challenge in diabetic care, with variable prognoses influenced by factors such as ulcer location, depth, and the presence of infection or ischemia. The Site, Depth, and Infection/Ischemia (SDI) classification system is a potential tool for predicting DFU outcomes, but its prognostic value requires further investigation. This retrospective cohort study, conducted at Qingdao Haici Hospital between January 2021 and December 2022, included 261 diabetic patients with DFUs located at or distal to the ankle joint. The SDI classification system was applied to categorize ulcers based on site, depth, and infection/ischemia. Patient outcomes, including healing time, minor and major amputations, and mortality, were assessed, with follow-up conducted through telephone or outpatient visits. Statistical analysis was performed using SPSS version 27, with p-values < 0.05 considered statistically significant. The study included 240 patients after exclusions. Significant differences in healing time, amputation rates, and mortality were observed across different SDI classifications. Patients with hindfoot ulcers (S3) had the longest healing time (9.3 months) and the highest mortality (23.1%). Deeper ulcers (D3) also exhibited longer healing times (4.3 months) and higher mortality (18.5%). Patients with both infection and ischemia (I3) had the longest healing time (5.6 months), highest amputation rates, and increased mortality. Statistical analyses revealed significant differences in healing time (p < 0.001), amputation rates (p = 0.000), and mortality (p = 0.017) across classification groups. The SDI classification system effectively predicts outcomes in DFU patients, with higher SDI grades associated with longer healing times, higher amputation rates, and increased mortality. This study highlights the clinical utility of the SDI system and underscores the need for its further implementation in clinical practice for better patient management and prognostic assessment.